2006
DOI: 10.1525/mp.2006.23.5.407
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Repeated Exposure on Liking and Judgments of Musical Unity of Intact and Patchwork Compositions

Abstract: This study examined the effects of repeated hearings on 74 participants’ responses to two types of musical compositions. Intact compositions consisted of short classical piano solos. Patchwork compositions were created by combining excerpts from three different musical works. The findings showed that listeners’ ratings of unity and liking for intact compositions were initially higher than those for patchwork compositions. With repeated hearings, however, ratings of patchwork compositions increased linearly whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

4
29
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(33 citation statements)
references
References 31 publications
4
29
0
Order By: Relevance
“…Regarding the question of how exposure to structured music relates to the development of knowledge and affect, one possibility is that repeated listening of music leads to both knowledge and preference formation. This is consistent with several studies showing the effects of mere exposure on preference for artificial visual stimuli (e.g., Zajonc, 1968), and effects of mere exposure on preference for musical compositions (Peretz, Gaudreau, & Bonnel, 1998; Tan, Spackman, & Peaslee, 2006). In particular, Tan et al showed a mere exposure effect, as indicated by increased preference ratings, after exposure to short complex compositions; in contrast, preference ratings decreased with repeated exposure for short, simple compositions, in line with the two-factor theory proposed by Berlyne (1971).…”
supporting
confidence: 92%
“…Regarding the question of how exposure to structured music relates to the development of knowledge and affect, one possibility is that repeated listening of music leads to both knowledge and preference formation. This is consistent with several studies showing the effects of mere exposure on preference for artificial visual stimuli (e.g., Zajonc, 1968), and effects of mere exposure on preference for musical compositions (Peretz, Gaudreau, & Bonnel, 1998; Tan, Spackman, & Peaslee, 2006). In particular, Tan et al showed a mere exposure effect, as indicated by increased preference ratings, after exposure to short complex compositions; in contrast, preference ratings decreased with repeated exposure for short, simple compositions, in line with the two-factor theory proposed by Berlyne (1971).…”
supporting
confidence: 92%
“…This is in contrast, however, with a number of findings that are consistent with a "mere exposure" effect of repetition, whereby music compositions of any kind are expected to be perceived as more pleasing over time simply due to exposure to the stimulus (Bornstein, 1989;Peretz, Gaudreau, & Bonnel, 1998;Zajonc, 1968). Hence, in line with the findings of Tan et al (2006) we can expect people's liking for popular music to change over repeated hearings, but this may depend on whether song sections are intact or rearranged. Intact versions of pop-rock songs may be preferred initially over restructured versions, but this may reverse with repeated hearings.…”
mentioning
confidence: 48%
“…Tan, Spackman, and Peaslee (2006) found that while people initially preferred intact versions over "patchwork" versions, they instead preferred the "patchwork" compositions after only four hearings. The authors reasoned that while the new arrangements were perceived as more complex and unpredictable initially, they came to be liked more over repeated hearings as they became more familiar to the listener.…”
mentioning
confidence: 97%
“…By contrast, for music heard in the background (i.e., incidental listening), multiple exposures lead to liking ratings that increase in tandem with recognition (Szpunar et al, 2004, Experiment 2), presumably because the exposure process (i.e., decreasing arousal potential) is slower when the perceiver's attention is diverted. To date, evidence of an interaction between quantity (frequency of exposure) and quality (focused or incidental) of the listening experience on liking for real music comes primarily from a single report (Szpunar et al, 2004; but see also Tan, Spackman, & Peaslee, 2006). Although the findings with impoverished and neutral stimuli are interesting theoretically, response patterns to real music are more relevant to the formation of music preferences in everyday life.…”
mentioning
confidence: 99%